Political and Legal Reconstruction of the Urgency that Forces the Issuance of PERPPU in Indonesia Based on Fair Benefit Values - Indra Utama Tanjung; Mhd Syahnan; Akmaluddin Syahputra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Legal sovereignty in Indonesia places the 1945 Constitution as the highest norm, which is the basis for other legislation. In the legal hierarchy, PERPPU is an executive product issued based on presidential prerogative in times of urgent and compelling circumstances. This research aims to examine the position of PERPPU, especially PERPPU No. 2 of 2022, in the context of a compelling emergency in accordance with Article 22 paragraph (1) of the 1945 Constitution. This study uses quantitative and juridical-normative methods to explore the application of PERPPU in legal practice, taking into account the complexity of social phenomena and normative values, including doururiah in Islamic law. A multidisciplinary approach is applied, involving theories from figures such as Amartya Sen, John Locke, and Montesquieu, as well as the principles of the Rule of Law. Primary and secondary data were analyzed through document studies, semi-structured interviews and field observations. The research results show that PERPPU No. 2 of 2022 concerning Job Creation, which was issued as a response to urgent global economic conditions, fulfills the requirements of compelling urgency as mandated by the 1945 Constitution. However, the publication process raises concerns about subjectivity and potential abuse of power. The DPR's approval of the PERPPU represents a constitutional step in the right direction, but broader involvement of stakeholders and transparency of the process are essential to ensure fairness and compliance with the principles of the rule of law. PERPPU, as an instrument issued in urgent circumstances, must be managed strictly and only used as a last resort. The involvement of the DPR in the approval process is an important democratic control, but it must be carried out efficiently to avoid a legal vacuum. Transparency in the process of determining and evaluating compelling emergencies is critical to maintaining the integrity of the legal system and public trust. This research suggests the need for reform in PERPPU issuance procedures to ensure that each publication is based on objective and urgent needs, by avoiding broad interpretations that could lead to abuse of power.